Formability of chromate conversion coating on zinc electroplated steel sheet - Hamid, N. H. B.; Hamzah, Esah (WIT Press, Southampton, ROYAUME-UNI (1999) (Monographie), 1999)
A conversion coating is a coating produced by chemical or electrochemical treatment of a metallic surface that gives a superficial layer. This layer which is actually a compound of the metal gives corrosion protection and guarantee paint adhesion. A chromating liquid for forming the chromate film was prepared. The solution is a mixture of Cr+6 and Cr+3 at a ratio of 1.5 to 2.0, 1-20g/l of H2S04, 1-20g/1 of HNO3, 1-20 ml NaOH and 1-10% Si oil. The solution was applied on a surface of zinc-based plated steel sheet of approximately 0.25 mm thickness and then dried. The chromate film formed on the sheet surface was approximately 0.5-1.0 Î¼m in thickness. The steel sheet with chromate film was then analysed and mechanically tested. It was found that the chromate solution has better stability over wide range of pH and the formability of its film is improved whence providing a better corrosion resistivity.